Construction of human activity‐based phosphorylation networks. Issue 1 (2nd April 2013) - Newman, Robert H; Hu, Jianfei; Rho, Hee‐Sool; Xie, Zhi; Woodard, Crystal; Neiswinger, John; Cooper, Christopher; Shirley, Matthew; Clark, Hillary M; Hu, Shaohui; Hwang, Woochang; Seop Jeong, Jun; et al.
<x xml:space="preserve">Abstract</x> The landscape of human phosphorylation networks has not been systematically explored, representing vast, unchartered territories within cellular signaling networks. Although a large number of in vivo phosphorylated residues have been identified by mass spectrometry (MS)‐based approaches, assigning the upstream kinases to these residues requires biochemical analysis of kinase‐substrate relationships (KSRs). Here, we developed a new strategy, called CEASAR, based on functional protein microarrays and bioinformatics to experimentally identify substrates for 289 unique kinases, resulting in 3656 high‐quality KSRs. We then generated consensus phosphorylation motifs for each of the kinases and integrated this information, along with information about in vivo phosphorylation sites determined by MS, to construct a high‐resolution map of phosphorylation networks that connects 230 kinases to 2591 in vivo phosphorylation sites in 652 substrates. The value of this data set is demonstrated through the discovery of a new role for PKA downstream of Btk (Bruton‧s tyrosine kinase) during B‐cell receptor signaling. Overall, these studies provide global insights into kinase‐mediated signaling pathways and promise to advance our understanding of cellular signaling processes in humans.